A nomogram to predict 28-day mortality in patients with sepsis combined coronary artery disease: retrospective study based on the MIMIC-III database - Gu, Quankuan; Huang, Ping; Yang, Qiuyue; Meng, Xianglin; Zhao, Mingyan (Frontiers in Medicine, 2024)
Object ： Establish a clinical prognosis model of coronary heart disease(CHD) to predict 28-day mortality in patients with sepsis. Method：The data were collected retrospectively from septic patients with a previous history of coronary heart disease(CHD) from the Medical Information Mart for Intensive Care(MIMIC)-III database. The included patients were randomly divided into the training cohorts and validation cohorts. The variables were selected using the backward stepwise selection method of Cox regression, and a nomogram was subsequently constructed. The nomogram was compared to the Sequential Organ Failure Assessment(SOFA) model using the C-index, area under the receiver operating characteristic curve(AUC) over time, Net reclassification index(NRI), Integrated discrimination improvement index(IDI), calibration map, and decision curve analysis(DCA).Result： A total of 800 patients were included in the study. We developed a nomogram based on age, diastolic blood pressure(DBP), pH, lactate, red blood cell distribution width(RDW), anion gap, valvular heart disease, peripheral vascular disease, and acute kidney injury(AKI) stage. The nomogram was evaluated using C-index, AUC, NRI, IDI, calibration plot, and DCA. Our findings revealed that this nomogram outperformed the SOFA score in predicting 28-day mortality in sepsis patients.